Diagnosis of pulmonary aspergillosis-related broncholithiasis in a child undergoing bronchoscopy: A case report. Issue 10 (March 2019) - Meng, Chen; Zhang, Zhongxiao; Liu, Xia; Yan, Xiuli; Shi, Chong; Liu, Na; Wang, Xinxin; Ma, Jing
Abstract: Rationale: Broncholithiasis is a rare disease and is characterized by calcification in the tracheobronchial tree. This disease has a predilection in the adult and occurrence is rare in children. Considering its infrequency, we report a rare clinical case, with the aim of sharing our experience during the diagnosis and treatment procedures. Patient concerns: We report a 9-year- and 6-month-old girl who complained of chronic cough and recurrent wheeze for 2 months. Diagnosis: Bronchialithiasis were found under bronchoscope. Pathologic examination revealed aspergillosis. Interventions: The stone and surrounding granulation tissue were removed using a bronchoscope and the patient was treated with antifungal therapy. Outcomes: The patient was in good general health without any clinical symptoms during the follow-up period. Lessons: Pulmonary Aspergillus infection can cause bronchiolithiasis. Stones were removed under bronchoscope, and anti- Aspergillus therapy was effective.